1983
DOI: 10.1051/rnd:19830703
|View full text |Cite
|
Sign up to set email alerts
|

Circadian changes in the abomasal secretions of the preruminant calf

Abstract: Summary. The purpose of this study was to investigate the circadian changes in the abomasal secretions (quantities of juice, enzymes and electrolytes) of the preruminant calf. The gastric juice was collected every hour from five calves fitted with an innervated abomasal pouch and given milk twice daily, with a 7-h interval between the morning and the evening meals.The amounts of gastric secretions produced were steady during 24 h, except for changes after the meals. The morning meal caused a considerable incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
4
1
1
Order By: Relevance
“…However, acetic and butyric acid concentration in the rumen 2 h after feeding was not different between the LFD and HFD diet (Korczyński, 2000). In this study Clion output was higher than measured in preruminat calves (Guilloteau and Toullec, 1983). Moreover, we cannot confi rm the fi ndings of mentioned authors who postulated the cyclic variations of the Cllevel in abomasal juice (data not shown).…”
Section: Discussioncontrasting
confidence: 81%
“…However, acetic and butyric acid concentration in the rumen 2 h after feeding was not different between the LFD and HFD diet (Korczyński, 2000). In this study Clion output was higher than measured in preruminat calves (Guilloteau and Toullec, 1983). Moreover, we cannot confi rm the fi ndings of mentioned authors who postulated the cyclic variations of the Cllevel in abomasal juice (data not shown).…”
Section: Discussioncontrasting
confidence: 81%
“…Studies performed by Thivend et al (1980) in several preruminant species have also shown that the digestive enzyme system is not yet completely developed in the newborn animal. Thus, the activity of these enzymes is low at birth, although the concentration of both total protein and individual pancreatic enzymes increase thereafter, with advancing age (Guilloteau & Toullec, 1983;Gusakov & Kurishka, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…3.i / Sécrétions digestives et repas L'augmentation du volume du suc gastrique sécrété et de son contenu (électrolytes dont HCI, chymosine et pepsine) au cours des 2 à 3 h qui suivent le repas (Guilloteau et Toullec 1983) est à relier avec l'accroissement postprandial du taux de gastrine (Bloom et al 1978, Toullec et al 1992) (figure 2).…”
Section: / Régulation Des Sécrétions Digestives : Exemplesunclassified